(untitled) (World Science, 2018)
The preambule gives the reasons for the relevance of the problem of experiencing the loss and grief of the perished law enforcers` wives in Ukraine, providing them with psychological counseling and the necessary psychological assistance based on the modern scientific heritage, world and local practical experience. The aim of the study is to examine the theoretical and practical approaches of providing psychological assistance to widows, as well as to analyze the impact of psychological assistance on the overall level of adaptive grieving. The main part reveals the main theoretical and practical approaches to the definition of varieties, structure and content of systemic psychological support based on extreme psychology and crisis intervention. It was noted the necessity of providing emotional support and psychological assistance at the early stages of experiencing grief and loss. It presents the brief description of the factors influencing psychological state of the person, who is in an emergency situation - the sudden death of a loved one. The concept of adaptive and non-adaptive ways of responding to stress factors, based on a study by E. Lindemann, is considered. Psychological reactions are described that correspond to different phases of a crisis state after a traumatic event, accordingly to the studies of D. Aguilera and J. Messick. The results of a comparative experimental psychological examination of the perished law enforcers` wives are set out in order to determine the significance of individual factors of socio-psychological adaptation for the formation of effective psych correctional programs. Statistically reliable data on the impact of psychological support on the general level of socio-psychological adaptation are obtained. In conclusion, it is stated the reasonability of providing the psychological assistance in case of loss, taking into account the hierarchy of personal problems. Experimentally proven that, when providing systemic psychological assistance, there is a tendency towards to of adaptability and emotional comfort indicators, decrease of level and moving away from problem situations avoidance.